2013
DOI: 10.1194/jlr.m034876
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cholesterol crystals and crown-like structures distinguish NASH from simple steatosis

Abstract: We sought to determine whether hepatic cholesterol crystals are present in patients or mice with nonalcoholic fatty liver disease/nonalcoholic steatohepatitis (NASH), and whether their presence or distribution correlates with the presence of NASH as compared with simple steatosis. We identifi ed, by fi lipin staining, free cholesterol within hepatocyte lipid droplets in patients with NASH and in C57BL/6J mice that developed NASH following a highfat high-cholesterol diet. Under polarized light these lipid dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
191
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(220 citation statements)
references
References 27 publications
17
191
1
3
Order By: Relevance
“…A morphometric study of liver biopsies demonstrated cholesterol crystals in lipid droplets in patients with steatohepatitis but not steatosis 199 . Statin use is safe in patients with liver disease 200 and a Cochrane review concluded that statins can improve steatosis and reduce aminotransferase levels but treatment trials with histological endpoints are lacking 201 .…”
Section: [H2] Reducing Injurymentioning
confidence: 96%
“…A morphometric study of liver biopsies demonstrated cholesterol crystals in lipid droplets in patients with steatohepatitis but not steatosis 199 . Statin use is safe in patients with liver disease 200 and a Cochrane review concluded that statins can improve steatosis and reduce aminotransferase levels but treatment trials with histological endpoints are lacking 201 .…”
Section: [H2] Reducing Injurymentioning
confidence: 96%
“…The fatty acid composition and the accumulation of free cholesterol have been implicated in playing a critical role in the development of NASH since an altered lipidome [3,11,12] as well as free cholesterol, positively correlate with the severity of NASH [10,12,28,29] . Dietary cholesterol may play a role in NAFLD onset [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations also highlighted the accumulation of free cholesterol as an important trigger for the progression from simple steatosis to severe NASH [9][10][11] . In fact, dietary cholesterol was demonstrated to be a critical factor in the progression of NASH [10,12] . Cholesterol fed to LDLR -/-mice induced a prominent inflammatory response, whereas high fat feeding without cholesterol induced steatosis in the absence of inflammation [13] .…”
Section: Introductionmentioning
confidence: 99%
“…What is less clear is how liver macrophages behave during the disease progression particularly in relation with the development of fibrosis (Tacke and Zimmermann, 2014). Recent studies have pointed out that hepatic macrophages in human NASH, but not in patients with simple steatosis often cluster around lipid droplets derived from death hepatocytes forming crown-like aggregates similar to those present in the inflamed visceral adipose tissue of obese patients (Rensen et al, 2009, Caballero et al, 2012and Ioannou et al, 2013. Furthermore, these macrophages appear enlarged and contained lipid vesicles and cholesterol crystals resembling foam cells of atherosclerotic plaques (Ioannou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have pointed out that hepatic macrophages in human NASH, but not in patients with simple steatosis often cluster around lipid droplets derived from death hepatocytes forming crown-like aggregates similar to those present in the inflamed visceral adipose tissue of obese patients (Rensen et al, 2009, Caballero et al, 2012and Ioannou et al, 2013. Furthermore, these macrophages appear enlarged and contained lipid vesicles and cholesterol crystals resembling foam cells of atherosclerotic plaques (Ioannou et al, 2013). Interestingly, clusters of foamy macrophages are also evident in several mice models of experimental NASH in association with lobular inflammation and hepatic fibrosis (Itoh et al, 2013 andIoannou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%